The question concerning human action - Bronisław Bombała (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The paper presents phenomenological and hermeneutical approach of human action in 20th century. There were two important cultural phenomena in the twentieth century. On the one hand, the growing expansion of technopoly, which based its operation on instrumental rationality and therefore affected destructively the spiritual realm of man, was growing, on the other hand, there were attempts to apply to the economy  humanistic and personalistic vision of management, based on axiological rationality. Studies and projects belonging to humanistic stream are based on the assumption that at turning points of history human labour became deprived of its human nature. Hermeneutical and phenomenological analysis  allows to indicate the sources of this dehumanization. Phenomenological analysis has discovered that in a technopoly human being has been deprived of her/his transcendental dimension and reduced to one of the factors of production. Hermeneutical analysis has discoverd eidos of human action: Norwid's church of work, Brzozowski's creation of will, Teilhard de Chardin' a holy march of mankind,  and Tymieniecka's the human creative act. The essence of the phenomenological approach of human action is to build a "community of work" that allows personal development through work as well as cooperation.